A study on ethics for medical practitioners in Malaysia / Azila Amiruddin and Hazwani Senafi - Amiruddin, Azila; Senafi, Hazwani (2008)
Nowadays, the rapid advancement in medical, science and technology have turn out to be an important issue in relation to the medical profession. However, the consequences of this advancement create several ethical dilemmas faced by the medical practitioners such as in relation to the ethical question on organ transplant, abortion, euthanasia and so forth. Generally, these ethical questions are so much related to the issue of abusing human body thus resulting harmful effects toward the patients and patient relatives. By conducting this research, we would like to analyse and evaluate the scope of law towards the ethical issues in medical field that arise out of the advancement in medical science and technology. In addition, we would like to determine the adequacy of the law provided in protecting the medical practitioners and the patients in Malaysia as to establish whether it is sufficient or otherwise. This research also includes several recommendations and suggestions in relation to the issues on this matter. The scope of the research will seek to clarify the position of our local law on the area of ethical issue in relation to the abusing of the human body with a view to assist the Malaysian Legislature in the area of developing a law. The insertion of the new provisions in the Act, regarding the ethical dilemmas of medical practitioners is necessary to increase the public awareness and thus decrease the rate of medical negligence act cases.